Productivit & Psychology Well Being - Ananda Tri Wahyuni; Feri Sadili; Novia Jamilati; Mochammad Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Productivity is generally defined as the relationship between output (goods or services) and input (labor, materials, money). Productivity is a measure of productive efficiency. According to Ryff (1989: 1.080) quoted from Devi Tri Wahyuningtiyas' research (2016) psychological well-being is a term used to describe individual psychological health based on fulfilling positive psychological functioning criteria. In this writing using the method of writing literature (Library Research). Writing is done by collecting data contained in literature books and other reading sources related to the problem under study. In this writing, secondary data was found and collected by conducting literature studies, namely collecting data based on literature books. The data obtained will be analyzed qualitatively, namely the analysis carried out by understanding and assembling the data that has been collected and arranged systematically, then a conclusion is drawn.